THE EMERGENCE AND DEVELOPMENT STAGES OF THE CONCEPT OF "COMPETENCE" IN EDUCATION - O. Sh. Uralov (Bright Mind Publishing, 2025)
The concept of "competence" has become a key element in modern educational systems, emphasizing an individual’s ability to effectively perform specific tasks based on knowledge, skills, and competencies. This paper traces the historical development of the concept of competence, its introduction into the educational sphere, and its subsequent evolution in pedagogical practice. Initially introduced in linguistics by Noam Chomsky in the 1960s, the concept of competence later expanded into educational theory and practice. The article explores the key stages of the development of competency-based approaches in education, from their theoretical foundations in the 1970s to their institutionalization in educational systems during the 1980s and 1990s. Furthermore, it examines the formation of competency-based educational models in the early 21st century, where emphasis shifted from theoretical knowledge to practical application. The paper also discusses the modern use of competency-based approaches in various educational contexts, focusing on disciplinary, social, and personal competencies, and highlights their role in shaping an individual’s capacity to function effectively in society. The study concludes that competency-based education is instrumental in enhancing the quality and effectiveness of education, fostering lifelong learning, and preparing individuals to meet the challenges of a rapidly changing global landscape.
Keywords: Competence, competency-based education, educational systems, pedagogical practice, social competence, personal competence, 21st century education.